International Treaty Enforcement between Constitutional Text and Institutional Practice: A Defense of Functional Pluralism in the Korean Model - Heikal, Sherif (Journal of Legal Sciences, 2025)
This research examines South Korea’s treaty incorporation methods by showing that its monist constitutional framework under Article 6(1) grants treaty laws domestic effect yet functional pluralism exists in practice. The courts use treaties at different levels of directness based on the nature of the subject matter and the clarity of the norms and the level of legislative backing. The Korean National Assembly maintains minimal involvement in treaty matters after the ratification process while the lack of a defined self-execution doctrine leads to inconsistent legal application and unclear interpretations. It should be noted that this research positions Korea within global constitutional pluralism through comparative analysis with Japan and four European nations (France, Germany and the United Kingdom) to show how treaty incorporation depends on judicial discretion and legislative involvement and institutional coordination. This research proposes specific reforms to clarify judicial enforceability standards and boost legislative involvement to achieve better doctrinal consistency and institutional alignment. Hence, this research presents Korea’s treaty integration system as a practical pluralist model which follows modern global constitutional developments.